2020
DOI: 10.1186/s41239-020-00226-x
|View full text |Cite
|
Sign up to set email alerts
|

Technology-supported management education: a systematic review of antecedents of learning effectiveness

Abstract: This paper provides a systematic, multidisciplinary review of antecedents of the effectiveness of technology-supported management learning and highlights potential directions for future research. Passive knowledge acquisition in physical classrooms is no longer the hallmark of higher education. Instead, the introduction of new technologies allows for active knowledge construction in increasingly virtual spaces. Such changes in the learning environment affect the education of the managers of tomorrow. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 95 publications
(279 reference statements)
1
25
0
2
Order By: Relevance
“…Furthermore, the data suggest that removing the discussion component of interteaching is likely to limit the effectiveness of the approach substantially (e.g., Garcia et al, 2016 ). This notion is in line with recent studies on the effectiveness of active learning components across in-person and online settings (Gayman et al, 2018 ; Müller & Wulf, 2020 ; Pollock et al, 2011 ). Overall, discussions seem to improve academic performance via enabling comparison and knowledge exchange between students, revision of previous content, and promoting critical thinking and higher-order learning (Gayman et al, 2018 ; Müller & Wulf, 2020 ; Pollock et al, 2011 ).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the data suggest that removing the discussion component of interteaching is likely to limit the effectiveness of the approach substantially (e.g., Garcia et al, 2016 ). This notion is in line with recent studies on the effectiveness of active learning components across in-person and online settings (Gayman et al, 2018 ; Müller & Wulf, 2020 ; Pollock et al, 2011 ). Overall, discussions seem to improve academic performance via enabling comparison and knowledge exchange between students, revision of previous content, and promoting critical thinking and higher-order learning (Gayman et al, 2018 ; Müller & Wulf, 2020 ; Pollock et al, 2011 ).…”
Section: Discussionsupporting
confidence: 87%
“…The COVID-19 pandemic has accelerated the development and adoption of new technologies in HE. In light of this trend, it is important to understand the role of technology and how it can be effectively utilised in the classroom (Müller and Wulf, 2020). Given learners' increased daily exposure to technology, we think it essential to examine how they perceive the now ubiquitous presence of technology-based practice in the classroom.…”
Section: The Perception Of the Use Of Technology In Higher Educationmentioning
confidence: 99%
“…Many studies of the effectiveness of technologies in education have shown minimal and sometimes null results. This is not surprising as technology does not of itself produce learning; it simply amplifies and extends instructional strategies (Müller, & Wulf, 2020). Too often, studies of technology effectiveness have paid inadequate attention to the content of the instruction and assumed that any technological strategy to amplify it would be effective.…”
Section: Literature Reviewmentioning
confidence: 99%